Participation of Users in the Development of the Information Architecture of a Telecare Application for Smartphones Based on the Card Sorting Method - Delgado, Cristina Nieves Perdomo [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Zitkus, Emilene (Springer Nature, 2022)
Access to new technologies by the elderly is gradually increasing. However, although more and more people make use of technology to improve their day-to-day, there are still problems that affect the accessibility and usability of these systems. The objective of this study has been to describe the process, analysis, results, and implication of a card sorting as a usability study to obtain relevant information for the decision making of the information architecture in the development of Telecare applications. The study has involved ten elderly people using the card sorting method in which users are given a predetermined set of category names and asked to sort individual cards into these predetermined categories, related to the telecare application. While the participants placed the cards, the method of thinking aloud was also used to have a view of two cognitive processes of the participant during the execution of the task, generating qualitative knowledge. Most of the participants showed confusion due to the terminology of the different functions of the application. The categories in which the participants had the most difficulty was in the registration and application configuration area. In general, the card sorting process can be considered a very useful technique in information architecture when designing a technological interface, as it is applied to understand how future users think about the content and usability of the system/service.
Keywords: Elderly; Telecare; Usability